Etiology and medical management of NEC. (June 2016) - Gupta, Amit; Paria, Anshuman
Abstract: Necrotising enterocolitis (NEC) is a serious infection of the bowel that predominantly affects preterm infants and is a leading cause for mortality and morbidity in preterm infants. It involves a spectrum of pathology including widespread inflammation of the intestinal mucosa, invasion of the immature gut by enteric gas forming bacteria, dissection of the gut wall and portal veins by this gas, often culminating in ischemic necrosis of the intestine. This article provides an overview of the incidence, etio-pathological risk factors, preventive strategies and medical management of NEC.